Climate change and small-scale fishing in South Africa: a community scale social vulnerability assessment for the southern Cape handline fishery - Andra, Kayla (Department of Biological Sciences, 2023)
Climate change is majorly affecting the quality and quantity of marine organisms, as well as people's livelihoods. Coastal communities, small-scale fishers, and fishing-reliant individuals are especially vulnerable to climate change impacts (and other stressors) that alter the state and availability of ocean resources. Therefore, implementing integrated management approaches (such as the Ecosystem Approach to Fisheries (EAF)) is crucial to address these vulnerabilities. This study concerns the vulnerability to the impacts of climate change of fishers who act as crew members in the southern Cape commercial handline fishery. The southern Cape is a rural, peri-urban, and urban region characterised by agriculture, fishing, tourism, and retirement services as major economic activities. Aside from their documented social, governance, and economic stressors, small-scale fishers in the southern Cape also face biophysical stress (i.e., changes in wind, rainfall, and sea state). The Global learning for understanding local solutions (GULLS) survey instrument and a social vulnerability framework were created to assess vulnerability and its comprising concepts (sensitivity, exposure, and adaptive capacity) for coastal communities experiencing notable climate change. This study presents the first quantitative analysis of the data collected in the southern Cape in 2014-15. Univariate and multivariate analyses were performed to answer four key questions to investigate whether social vulnerability (as well as sensitivity, exposure, and adaptive capacity) differed among the communities, how variable vulnerability is within the communities, what drives the differences among the communities and to gain insight on the implications for issues of scales. The fishing communities differed significantly in their overall social vulnerability scores. Sensitivity and exposure were similar between the fishing communities. Sensitivity was the main driver of vulnerability for all fishers due to their attachment to fishing as an occupation, low self-sufficiency, and attachment to their communities. There was no significant difference in the dispersion (homogeneity) of the fishers' responses within the communities. The results also corroborate previous qualitative research, showing that variations between the communities are driven by adaptive capacity. The “component” scale (the second scale of the four-scale GULLS framework) yielded the most beneficial results and is recommended for future analyses. In addition, recommendations are made for future surveys to address uneven weighting, fundamental system changes (such as COVID-19), and questions irrelevant to the southern Cape small-scale fishers. Overall, with these recommendations, an improved survey offers a quicker methodology that can easily be communicated with various decision-makers and paves the way for consistent temporal comparisons that stimulate a long-term understanding of vulnerability. Most importantly, these recommendations and methods can contribute to the Ecosystem Approach to Fisheries (EAF) implementation in the southern Cape and the sustainability of this marine social-ecological system.